Kualitas Pelayanan Pinjaman Terhadap Kepuasan Anggota dan Implikasinya Terhadap Partisipasi Anggota Sebagai Debitur : Studi Pada Koperasi Pensiunan Wredatama Kabupaten Ngada Provinsi Nusa Tenggara Timur - Maria Fransiska Meliana; Rosti Setiawati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
The service quality of the Wedhatama Cooperative (KOPTAMA) is centered on efforts to fulfill the needs and desires of members and the provision of delivery to meet the expectations of members. Service quality depends on the ability of the service provider to consistently meet the expectations of members. The purpose of this study was to determine the effect of service quality on cooperative member satisfaction and its implications for member participation as debtors of the Wredatama Ngada Pension Cooperative. This study uses explanatory study methods (descriptive verification). The dimensions used in this study are Service Quality (SERVQUAL) (X) which consists of the variables Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5) which are associated with Member satisfaction variables. (Y) and Member Participation variable (Z) using simple linear regression and multiple linear regression. The results show that there is significance influence between service quality variables (Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) , and Empathy (X5) on member satisfaction and the effect of member satisfaction on member participation by 48.40%, while the remaining 51.6% is influenced by other variables not examined in this study.